What do parents want: Parental spousal preferences in China - Raiber, Eva et al (Economic Development and Cultural Change)
In many societies, parents are involved in selecting a spouse for their child, integrating this with decisions about premarital investment such as education. Do spousal preferences of parents and children conflict? We estimate parents$1 (Bspousal preferences based on survey choices between random profiles, elicited from parents or other relatives who actively search for a spouse on behalf of their adult child in Kunming, China. We simulate marriage outcomes based on preferences for age and education and compare them with patterns in the general population and with the preferences of a survey of students. The common concern that there may be aversion to highly educated or high-earning wives is somewhat corroborated in parents$1 (Bpreferences but not in students$1 (Bpreferences, nor in outcomes, where homogamy is common and wives who are more educated than husbands are as common as husbands who are more educated than wives. Parents prefer wives younger than their husbands, yet most couples are the same age, an outcome consistent with student preferences. Overall, divergences between parental and child preferences exist but are neither major nor very influential in explaining observed outcomes. Fears that highly educated women face diminished marriage prospects appear less serious than often claimed.- Reproduced s